2012
DOI: 10.1158/1055-9965.epi-11-0784
|View full text |Cite
|
Sign up to set email alerts
|

CpG Site–Specific Hypermethylation of p16INK4α in Peripheral Blood Lymphocytes of PAH-Exposed Workers

Abstract: Background: Sufficient epidemiologic evidence shows an etiologic link between polycyclic aromatic hydrocarbons (PAH) exposure and lung cancer risk. While the genetic modifications have been found in PAH-exposed population, it is unclear whether gene-specific methylation involves in the process of PAHassociated biologic consequence.Methods: Sixty-nine PAH-exposed workers and 59 control subjects were recruited. Using bisulfite sequencing, we examined the methylation status of p16INK4a promoter in peripheral bloo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 54 publications
1
43
0
Order By: Relevance
“…Promoter hypermethylation and reduced expression of the IFN γ gene (another gene commonly down-regulated in various cancers) was observed in Jurkat cells and two human adenocarcinoma cell lines exposed to low, non-cytotoxic doses (0.1 and 1 nM) of B a P, as well as in cord white blood cells of women who were exposed to PAHs during pregnancy [50]. Hypermethylation of CpG islands within the p16 INK4α tumor suppressor gene, as well as down-regulation of expression of the gene, was observed in human bronchial epithelial cells exposed to B a P [51]. The same trend was observed in the peripheral blood of PAH-exposed workers, relative to that of non-exposed control subjects, and the degree of methylation was associated with the internal exposure and the level of DNA damage).…”
Section: Epigenetic Effects Associated With Carcinogenic Chemicalsmentioning
confidence: 99%
“…Promoter hypermethylation and reduced expression of the IFN γ gene (another gene commonly down-regulated in various cancers) was observed in Jurkat cells and two human adenocarcinoma cell lines exposed to low, non-cytotoxic doses (0.1 and 1 nM) of B a P, as well as in cord white blood cells of women who were exposed to PAHs during pregnancy [50]. Hypermethylation of CpG islands within the p16 INK4α tumor suppressor gene, as well as down-regulation of expression of the gene, was observed in human bronchial epithelial cells exposed to B a P [51]. The same trend was observed in the peripheral blood of PAH-exposed workers, relative to that of non-exposed control subjects, and the degree of methylation was associated with the internal exposure and the level of DNA damage).…”
Section: Epigenetic Effects Associated With Carcinogenic Chemicalsmentioning
confidence: 99%
“…Dietary insufficiency of folate and other 1-carbon metabolism-dependent micronutrients, or germline or somatic mutations in members of the pathway can induce hypomethylation in tumor, and normal tissues including blood (4,14,25,26). Exogenous exposures, such as carcinogen exposure may influence methylation by inducing DNA damage or by affecting DNMT enzyme activity (4,11,27,28). Furthermore, the efficiency of DNA methylation may be affected by age (12,29).…”
Section: Causes and Consequences Of Genome-wide Hypomethylationmentioning
confidence: 99%
“…Methylation of different CpG sites may affect the binding of different transcription factors that mediate specific molecular pathways in the pathogenesis of HCC, and may also be influenced by these transcription factors. Recent studies have shown that INK4A DNA hyper-methylation is associated with environmental carcinogens [4750]. Levels and patterns of CpG methylation of INK4A DNA may therefore serve as a marker of both exposure and effect of HCC carcinogens.…”
Section: Discussionmentioning
confidence: 99%